The Effect of Educational Methods of Supply Chain Management on Conflict Management in Educational Environments - Hossein Amiri Dogahe; Hamideh Razmara Meydanghah; Mohammad Naghi Imani (International Journal of Supply Chain Management, 2019)
Abstract- Today, human resource is considered as the main asset of organizations and its competitive advantage and is one of the most valuable resources and capital of that organization. The purpose of this paper is to increase the understanding of the challenges and conflicts in sustainable supply chain management through empirical evidence. Therefore, the importance of attracting, retaining and empowering this capital has always been considered by the thinkers. One of the solemn factors in employee management is solving the conflict between them, which has been analyzed in this paper using inferential statistics. In order to determine the validity of the questionnaire, firstly, the number of items for each component was determined and the initial form of the questionnaire was prepared by evaluating the theoretical foundations and studies, as well as obtaining opinions from some experts. After this stage, several copies of the questionnaire were distributed to a number of experts, and they were asked to express their corrective comments regarding the questionnaire. The results show that there is a significant relationship between avoidance style and teachers performance, and there was no significant relationship between the managers 'mastery style on the teachers' performance.